2019
DOI: 10.1128/mbio.02289-19
|View full text |Cite
|
Sign up to set email alerts
|

The Immune Protein Calprotectin Impacts Clostridioides difficile Metabolism through Zinc Limitation

Abstract: Clostridioides difficile infection (CDI) is the leading cause of postantibiotic nosocomial infection. Antibiotic therapy can be successful, yet up to one-third of individuals suffer from recurrent infections. Understanding the mechanisms controlling C. difficile colonization is paramount in designing novel treatments for primary and recurrent CDI. Here, we found that limiting nutrients control C. difficile metabolism during CDI and influence overall pathogen fitness. Specifically, the immune protein CP limits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 69 publications
0
37
0
1
Order By: Relevance
“…Previously, our group demonstrated that calprotectin is an essential component of the innate immune response to CDI and calprotectin-mediated transition metal limitation is inhibitory to C. difficile growth (7). Furthermore, we showed that subinhibitory concentrations of calprotectin dramatically alter the transcriptional profile and metabolism of C. difficile in vitro (19).…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…Previously, our group demonstrated that calprotectin is an essential component of the innate immune response to CDI and calprotectin-mediated transition metal limitation is inhibitory to C. difficile growth (7). Furthermore, we showed that subinhibitory concentrations of calprotectin dramatically alter the transcriptional profile and metabolism of C. difficile in vitro (19).…”
Section: Discussionmentioning
confidence: 81%
“…ZupT has been reported in several studies to be one of the most highly upregulated genes in C. difficile during metal stress, suggesting this importer plays a key role in metal homeostasis for this important pathogen (19,21,22). However, despite this strong transcriptional response, inactivation of zupT does not completely inhibit the ability of C. difficile to colonize the host or grow in the presence of lower concentrations of calprotectin ( Fig.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations